Léxico e enunciação: a conceitualização do substantivo concreto. Questões para o ensino de línguas - Francisconi, Leonam Ricardo Alcantara [UNIFESP] (2020)
Functionalist studies of the last decades, in particular by Camacho, Dall'Aglio Hattnher & Gonçalves (2014), differ from what is recurring found in grammar reference books, by classifying nouns by their potential on being a referring expression. Thus, the referential potential of the noun is what activates its naming and referencing functions. However, in this classification, there is still a sense that it is inherent concerning the lexical unity. In the present study, according to the precepts of the Theory of Predicative and Enunciative Operations, we bring another conception for the sense of linguistic units. This conception is constructed by the main interactions observed in the enunciation. For this purpose, we take the noun ‘faca’, from Brazilian Portuguese lexical as an object of study. It is commonly categorized as a concrete noun, in order to comprehend the regularities that support the unit's referential potential, its functions of naming and referencing, as well as if it is open to possible conceiving it as a representative of this category. It is also intended to verify how the integration of the unit takes place in a sentence sustained by the process of constructing meanings. For such, we are examining, on the one hand, how the semantic specification of the verbal context by the noun occurs, and, on the other hand, how other constitutive elements in the same context may give determinations to the noun. In this particular case, we expect to explain accurately the processes of semantic variation, which is proper to the noun under analysis, in order to conceptualize it for theoretical and applied purposes in the field of language teaching.